2008
DOI: 10.1007/s11365-008-0091-2
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial intent in a transitional economy: an application of the theory of planned behavior to Romanian students

Abstract: This study examines entrepreneurial intent in Romanian students using the Theory of Planned Behavior (Ajzen, Adv. Exp. Soc. Psychol., 20:1-63, 1987). Using multiple regression analyses to test for mediation, we analyzed survey data from 324 Romanian students. Some of our findings were consistent with the Theory of Planned Behavior, while others were not. As expected, we found that self-efficacy and the desirabilities associated with creating a venture were positively related to entrepreneurial intent. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
151
3
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(189 citation statements)
references
References 26 publications
25
151
3
10
Order By: Relevance
“…According to Carr & Sequeira (2007) previous exposure to entrepreneurship, especially growing up in an entrepreneurial family, significantly influences attitudes toward entrepreneurship. This is also supported by a study on Romanian students (Shook & Bratianu, 2010), using the Theory of Planned Behaviour (TBP), whose results showed that self-efficacy and the social desirability were positively related to entrepreneurial intentions. In addition, practical exposure to entrepreneurship, by personal entrepreneurial experience, or the family entrepreneurship background, have been reported to impact positively on entrepreneurial intentions among students (Basu & Virick, 2008;Ahmed et al 2010).…”
Section: Literature Reviewsupporting
confidence: 53%
See 1 more Smart Citation
“…According to Carr & Sequeira (2007) previous exposure to entrepreneurship, especially growing up in an entrepreneurial family, significantly influences attitudes toward entrepreneurship. This is also supported by a study on Romanian students (Shook & Bratianu, 2010), using the Theory of Planned Behaviour (TBP), whose results showed that self-efficacy and the social desirability were positively related to entrepreneurial intentions. In addition, practical exposure to entrepreneurship, by personal entrepreneurial experience, or the family entrepreneurship background, have been reported to impact positively on entrepreneurial intentions among students (Basu & Virick, 2008;Ahmed et al 2010).…”
Section: Literature Reviewsupporting
confidence: 53%
“…Attitudes are supposed to be very good predictors of intentions, along with subjective norms, perceived self efficacy and feasibility of the planned entrepreneurial venture. There have been previous validations and applications of the model in the empirical research of youth entrepreneurial intentions (Carr & Sequeira, 2007, (Engle R. , et al, 2010; (Shook & Bratianu, 2010). On the other hand, the Shapero-Krueger model relies on propensity for behaviour, along with the perceived desirability and feasibility as fundamental direct predictors of entrepreneurial intentions.…”
Section: Literature Reviewmentioning
confidence: 98%
“…This suggests that, the intention of an individual to start a new venture not only depend on opinions of friends and family members, but also on external factors such as availability of funding and resources, presence of opportunity and on the perceived and actual competencies of the individual himself/herself. In a study on Romanian students, Shook and Bratianu (2010) reported a negative relationship between SN and EI. This implies that the less supportive important people are of a student, the more likely s/he would have an EI.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 97%
“…al 2015. Others find subjective norms have a significant negative effect (Shook and Bratianu, 2008) or no effect at all on entrepreneurial intention (Krueger et. al., 2000).…”
Section: Literature Reviewmentioning
confidence: 99%